Digital loneliness as a new diagnostic category in psychiatry: the impact of technology and social media use on psychological well-being - Szawarnoga, Daniel; Stasiniewicz, Artur; Fojcik, Joanna; Krzystanek, Marek (Frontiers in Psychiatry, 2025)
PurposeThe aim of this study was to determine the impact of social media use on users’ subjective feelings of loneliness and the occurrence of anxiety symptoms, taking into account demographic variables such as age and education level.Material and methodsA total of 220 patients of the Mental Health Outpatient Clinic participated in the study and completed a self-administered survey questionnaire including demographic data, social media use patterns and assessment of experienced psychological symptoms.ResultsStatistical analyses showed that younger users spend more time online, which correlates with higher feelings of loneliness and severity of anxiety symptoms, while higher levels of education are associated with less time online and better awareness of the dangers of excessive social media use.ConclusionsSocial media leads to an increased sense of isolation. Excessive use of these platforms is associated with decreased sleep quality, decreased self-esteem, increased levels of stress and anxiety and an overall deterioration in users’ mental health. The experience of digital loneliness varies according to the characteristics of users - young people, women and people with limitations are the most vulnerable to the negative effects of excessive social media use.